2021
DOI: 10.24292/01.ap.174171121
|View full text |Cite
|
Sign up to set email alerts
|

The analysis of alder pollen season in selected cities of Poland in 2021

Abstract: The study aims to monitor the alder pollen season in selected Polish cities: Bialystok, Cracow, Lublin, Olsztyn, Opole, Piotrkow Trybunalski, Sosnowiec, Szczecin, Warsaw, Wroclaw and Zielona Gora in 2021. Pollen concentrations were recorded by volumetric method using a Burkard-type sampler operating in a continuous volumetric mode. Alder pollen season, defined as the period with 98% of the annual total catch, started in 3rd decade of February in all monitoring sites. There was a marked variation in duration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…As shown by literature data, the concentrations of alder pollen grains in various regions of Poland in 2020 were quite low [33]. In 2021, high concentrations of pollen grains were noted in many Polish cities [34], also in Kielce. The concentration of alder pollen grains in Kielce in 2021 was similar to that of Alnus pollen in Piotrków Trybunalski [34].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As shown by literature data, the concentrations of alder pollen grains in various regions of Poland in 2020 were quite low [33]. In 2021, high concentrations of pollen grains were noted in many Polish cities [34], also in Kielce. The concentration of alder pollen grains in Kielce in 2021 was similar to that of Alnus pollen in Piotrków Trybunalski [34].…”
Section: Discussionmentioning
confidence: 78%
“…In 2021, high concentrations of pollen grains were noted in many Polish cities [34], also in Kielce. The concentration of alder pollen grains in Kielce in 2021 was similar to that of Alnus pollen in Piotrków Trybunalski [34]. The onset of the alder pollen season in Kielce in 2021 was similar to that recorded in Lublin, Białystok, and Kraków, whereas the end dates were similar to those noted in Lublin and Olsztyn [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alder pollen season in 2022 was characterized by substantially lower pollen concentrations than in 2021. As shown by the comparison of the results from 2019-2022, the lowest concentrations of alder pollen were usually recorded in Cracow and Sosnowiec, but not in 2022 [8][9][10]. In 2022, high and very high concentrations of alder pollen persisted over a greater number of days than in 2019-2021 in most cities.…”
Section: Discussionmentioning
confidence: 88%
“…The comparison of data from 2019-2022 showed that the alder pollen season typically began on different days of February. The season started at the end of January in 2020 and 2022 only in Szczecin [8][9][10]. In all the study years, the alder pollen season began earlier in the west of the country than in the eastern part.…”
Section: Discussionmentioning
confidence: 89%